2009
DOI: 10.1088/0004-637x/699/2/1573
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electron-Capture Supernovae: X-Ray Binaries in Starbursts

Abstract: We develop population models of high-mass X-ray binaries (HMXBs) formed after bursts of star formation and we investigate the effect of electron-capture supernovae (ECS) of massive ONeMg white dwarfs and the hypothesis that ECS events are associated with typically low supernova kicks imparted to the nascent neutron stars. We identify an interesting ECS bump in the time evolution of HMXB numbers; this bump is caused by significantly increased production of wind-fed HMXBs 20-60 Myr post-starburst. The amplitude … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 23 publications
7
39
0
Order By: Relevance
“…To examine the influence of different kinds of SNe on the orbital period distribution, we employ a Monte-Carlo method to simulate the formation of BeXBs. We adopt the binary population synthesis (BPS) code developed by Hurley et al (2000Hurley et al ( , 2002 to calculate the evolutions of a large number of the primordial binaries, which is similar to the code StarTrack used by Linden et al (2009). We consider solar abundance for the stars, with most of the input parameters (i.e., the distributions of the orbital separation, mass ratio, the initial mass function of the mass of the primary star) to be the same as the standard ones described by Hurley et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the influence of different kinds of SNe on the orbital period distribution, we employ a Monte-Carlo method to simulate the formation of BeXBs. We adopt the binary population synthesis (BPS) code developed by Hurley et al (2000Hurley et al ( , 2002 to calculate the evolutions of a large number of the primordial binaries, which is similar to the code StarTrack used by Linden et al (2009). We consider solar abundance for the stars, with most of the input parameters (i.e., the distributions of the orbital separation, mass ratio, the initial mass function of the mass of the primary star) to be the same as the standard ones described by Hurley et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of electron‐capture SNe, which naturally produce such NSs with lower velocity kicks was subsequently introduced by Podsiadlowski et al (2004). More recent evidence for low‐velocity kicks in binary systems has been inferred from the spin–eccentricity correlation seen in DNS binaries (Dewi, Podsiadlowski & Pols 2005; Faulkner et al 2005) and in a starburst activity of high‐mass X‐ray binaries in the Small Magellanic Cloud (Linden et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff corresponds both to the first appearances of electron-capture supernovae (ECS; Nomoto 1984;Poelarends et al 2008) in our simulations as well as the last ironcore collapse SN. In Linden et al (2009), we have found that ECS are highly associated with the production of Be-HMXBs. Regardless of the accuracy of this association, we note that McSwain & Gies (2005) found the observed number of Be-HMXBs to be greatest between 25 and 100 Myr after star formation, relegating the vast majority of Be-HMXB activity until after the end of the simulations and the questions considered here.…”
Section: Simulation Code and Modelsmentioning
confidence: 91%